Evaluation of cement stabilized recycled asphalt pavement/lateritic soil blends for soft soil improvement - SUKSAN Aniroot; HORPIBULSUK Suksun (Rock and Soil Mechanics, 2022)
This research evaluates the potential of cement stabilized recycled asphalt pavement (RAP)/marginal lateritic soil blends as stone column aggregate instead of the traditional quarry aggregate. The undrained shear response of the blended materials at various RAP replacement ratios and effective confining pressures are investigated. The RAP replacement ratios were 10%, 30% and 50% by dry weight and ordinary Portland cement contents were 1% and 3%. It was evident that RAP replacement increased large particles and meanwhile reduced fines particles; hence the increased compactibility. Under applied effective stress lower than pre-consolidation pressure, RAP-soil blends exhibited strain-hardening behavior associated with decreased pore pressure. The strain-softening behavior in stress-strain curve for cement stabilized RAP-soil blends was diminished when RAP replacement ratio increased. The role of cementation improved the cohesion while friction angle insignificantly unchanged. The strength and stiffness of cement stabilized RAP-soil blends is mainly dependent upon the cementation bond strength and RAP replacement ratio. Shear strength improvement increased with the increased RAP replacement ratio for both unstabilized and cement stabilized RAP-soil blends while stiffness of cement stabilized RAP-soil blends decreased due to high energy absorption of asphalt binder.